Estimation of changes in above-ground biomass and carbon stocks of mangrove forests using sentinel-2a in Thai Thuy district, Thai Binh province during 2015 - 2019 - Nguyen, Hai-Hoa; Bich, Nguyen Thi Ngoc; Nghia, Nguyen Huu; Lan, Tran Thi Ngoc; Nguyen, Thi Thu Hien; Dang, Hoang Vuong (Vietnam Journal of Science and Technology, 2022)
Mangrove forests are found along shallow shorelines with modest slopes where they receive freshwater runoff and nutrients from rainfall. They have been globally recognised as having a vital function in preventing coastal erosion, mitigating wave actions, and protecting coastal habitats and adjacent shoreline land-uses from extreme coastal events. Using Sentinel-2A, the spatial distribution of mangrove forests was constructed over three years. The accuracy assessment showed that the overall accuracy of the 2019 Sentinel-2A classification was 93.6 % with a Kappa coefficient of 0.90, and the accuracy of the Sentinel-2A in 2015 and 2017 was also more than 90.0 % with a Kappa coefficient of 0.87. There were 2327.9 ha of mangrove forests in 2019; 2007.9 ha in 2017; and 1881.3 ha in 2015. The AGB of mangrove forests in Thai Thuy has increased over time. In 2015, the area of mangrove forests with AGB higher than 7.3 tons ha-1 and AGC more than 3.42 tons ha-1 was estimated at about 877.2 ha, the area of mangrove forests with AGB and AGC greater than 7.3 and 3.42 tons ha-1, respectively, increased to 1067.6 ha in 2017, and there were 1241.1 ha with AGB over 7.3 tons ha-1 and AGC greater than 3.42 ton ha-1 in 2019. There were small variations of AGB and AGC of mangrove forests between field measurements and Sentinel-based estimation in 2019. Therefore, using Sentinel-2A to estimate AGB and AGC of mangrove forests is reliable and applicable to the Thai Binh coast and it needs to be tested in other similar coastal areas in Viet Nam.